Echocardiographic Evaluation of Ventricular Function—For the Neonatologist and Pediatric Intensivist - Tissot, Cécile; Singh, Yogen; Sekarski, Nicole (Frontiers in Pediatrics, 2018)
In the neonatal and pediatric intensive care setting, bedside cardiac ultrasound is often used to assess ventricular dimensions and function. Depending upon the underlying disease process, it is necessary to be able to evaluate the systolic and diastolic function of left and or right ventricles. The systolic function of left ventricle is mostly assessed qualitatively on visual inspection visually by “eye-balling” and quantitatively and by measuring circumferential fraction the shortening fraction on M-mode or calculating and the ejection fraction by Simpson’s planimetry. The assessment of left ventricular , whereas diastolic function relies essentially on the mitral valve and pulmonary venous Doppler tracings or and on Tissue Doppler evaluation. The particular right ventricular particular shape and anatomical position does not permit to use the same parameters for measuring systolic function as is used for the left ventricle. Tricuspid annular plane systolic excursion (TAPSE) and S’ velocitywave on tissue Doppler imaging areis more often being used for quantitative assessment of right ventricle systolic function.to assess right ventricular systolic function objectively. Several parameters are proposed to assess right ventricleular systolic function such as fractional area change (FAC), 3D echocardiography, speckle tracking and strain rate are being researched and myocardial performance index (MPI) or Tei index, which are often sued in research setting and normal values for children are being established. Diastolic function of right ventricle is evaluated by tricuspid valve and hepatic venous Doppler tracings or and on by Tissue Doppler evaluation. The normal values for children are pretty similar to adults while normal values for the neonates, especially preterm infants, may differ significantly from adult population. The normal values for most of the parameters used to assess cardiac function in term neonates and children have now been established. Normal values for children differ little from the adult norms.